Handbook for teaching statistics and research methods - Brewer, Charles L.; Ware, Mark E. (Lawrence Erlbaum Associates, 1999)
(from the preface) Both editions of this book contain numerous articles about teaching statistical concepts and tests, as well as techniques for generating data sets. Both editions emphasize approaches to teaching about the literature review and research design, as well as to using computers and promoting students' scholarly production. The present edition contains more articles about ethics in research and teaching ethics. All articles in this volume were previously published in "Teaching of Psychology."